PENGEMBANGAN BAHAN AJAR SISTEM KOLOID BERBASIS WEB BERBANTUAN APLIKASI EXE LEARNING - Wahyu Ningsih, Elen; Dewi Handayani; Nurhamidah (ALOTROP, 2024)
This study aims to develop a web-based colloid system teaching materials assisted by exe-learning applications. The development model used was the 4-D (Four-D) model which consists of the define, design, develop and disseminate stages. The research was conducted at SMA Negeri 2 Bengkulu Utara with the research subjects being 12 students of class XI MIPA 2 for the small-scale trial, and 34 students of grade XI MIPA 3 for the large-scale trial. The instruments used were interview sheets, questionnaires, material and media validation sheets, student and teacher response questionnaires, and pretest and posttest sheets. The results of this study indicate that the web-based colloid system teaching materials are very feasible by media experts and material experts with a percentage of 93.13% of media aspect and 86.42% of material aspect, student responses to web-based colloid system teaching materials are in the category of very good with an average percentage of 89.56%. Learning outcomes after using teaching materials developed increased with an average N-gain score of 0.67 on the medium criteria and the teacher's response to web-based colloid system teaching materials was in the very good category with an average percentage an average of 93.23%.